Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Response of Root Respiration to Warming and Nitrogen Addition Depends on Tree Species - T. J. Muratore; M. A. Knorr; M. J. Simpson; R. B. Stephens; R. P. Phillips; S. D. Frey (Global Change Biology, 2024)
Roots contribute a large fraction of CO 2 efflux from soils, yet the extent to which global change factors affect root‐derived fluxes is poorly understood. We investigated how red maple ( Acer rubrum ) and red oak ( Quercus rubra ) root biomass and respiration respond to long‐term (15 years) soil warming, nitrogen addition, or their combination in a temperate forest. We found that ecosystem root respiration was decreased by 40% under both single‐factor treatments (nitrogen addition or warming) but not under their combination (heated × nitrogen). This response was driven by the reduction of mass‐specific root respiration under warming and a reduction in maple root biomass in both single‐factor treatments. Mass‐specific root respiration rates for both species acclimated to soil warming, resulting in a 43% reduction, but were not affected by N addition or the combined heated × N treatment. Notably, the addition of nitrogen to warmed soils alleviated thermal acclimation and returned mass‐specific respiration rates to control levels. Oak roots contributed disproportionately to ecosystem root respiration despite the decrease in respiration rates as their biomass was maintained or enhanced under warming and nitrogen addition. In contrast, maple root respiration rates were consistently higher than oak, and this difference became critical in the heated × nitrogen treatment, where maple root biomass increased, contributing significantly more CO 2 relative to single‐factor treatments. Our findings highlight the importance of accounting for the root component of respiration when assessing soil carbon loss in response to global change and demonstrate that combining warming and N addition produces effects that cannot be predicted by studying these factors in isolation.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Sialic acid, the secret gift for the brain - Fan Liu; Anna Bella Simpson; Esmée D’Costa; Fanny Sophia Bunn; Sander S. van Leeuwen (Critical Reviews in Food Science and Nutrition, 2023)

Integrated Exposure–Response of Dupilumab in Children, Adolescents, and Adults With Atopic Dermatitis Using Categorical and Continuous Efficacy Assessments: A Population Analysis - Emily Briggs; Mohamed A. Kamal; Matthew P. Kosloski; Ian Linsmeier; Natalie Jusko; Nancy Dolphin; Jason Chittenden; Eric L. Simpson; Amy S. Paller; Elaine C. Siegfried; Brad Shumel; Noah A. Levit; et al. (Pharmaceutical Research, 2023)
Background While the majority of patients with atopic dermatitis (AD) achieve disease control with dupilumab treatment, there is variability in which patients achieve clear disease. The predictors of these responses are currently unclear. Integrated models were developed to evaluate the exposure–response (E-R) relationship of dupilumab in children, adolescents, and adults with AD. Methods Data from six Phase II and III clinical studies were pooled (2,366 adults [> 18 years], 243 adolescents [≥ 12 to < 18 years] and 359 children [≥ 6 to < 12 years]) for model development. Efficacy was assessed using the Eczema Area and Severity Index (EASI) and Investigator’s Global Assessment (IGA). Indirect response models were applied to link measures of efficacy and functional serum dupilumab concentrations. The covariates on individual placebo-corrected response were assessed. Clinical trial scenarios were simulated to compare E-R relationships across age groups. Safety was not explored. Results After correcting for differences in placebo response and dupilumab exposure: 1) older age, higher body weight, lower baseline thymus and activation-regulated chemokine, and Asian race were associated with slightly lower EASI response, and no clear covariates were identified on IGA response; 2) clinical trial simulations generally showed slightly higher response at a given dupilumab concentration in children compared to adults and adolescents with severe and moderate AD. Conclusions The collectively tested covariates explain some of the variability in dupilumab response in patients with AD. Patients in all age groups showed adequate response to dupilumab; however, children showed slightly higher drug effects compared to adults and adolescents at equivalent concentrations.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

A metagenomic-based study of two sites from the Barbadian reef system - S. Simpson; V. Bettauer; A. Ramachandran; S. Kraemer; S. Mahon; M. Medina; Y. Vallès; V. Dumeaux; H. Vallès; D. Walsh; M. T. Hallett (Coral Reefs, 2023)
We study the microbiome of sea water collected from two locations of the Barbadian coral reefs. The two sites differ in several environmental and ecological variables including their endogenous benthic community and their proximity to urban development and runoffs from inland watersheds. The composition of the microbial communities was estimated using whole genome DNA shotgun sequencing with adjuvant measurements of chemical and environmental qualities. Although both sites exhibit a similar degree of richness, the less urbanized site (Maycocks reef at Hangman’s Bay) has a strong concentration of phototrophs whereas the more urbanized location (Bellairs reef at Folkstone) is enriched for copiotrophs, macroalgal symbionts and marine-related disease-bearing organisms from taxa scattered across the tree of life. Our results are concordant with previous profiles of warm ocean surface waters, suggesting our approach captures the state of each coral reef site, setting the stage for longitudinal studies of marine microbiome dynamics in Barbados.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Land Use History Mediates Soil Biogeochemical Responses to Drought in Temperate Forest Ecosystems - Ernest D. Osburn; Julia S. Simpson; Brian D. Strahm; J. E. Barrett (Ecosystems, 2022)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Validated Guidelines for Simulating Centrifugal Blood Pumps - Clayton S. Semenzin; Benjamin Simpson; Shaun D. Gregory; Geoff Tansley (Cardiovascular Engineering and Technology, 2021)

Zircon petrochronology in large igneous provinces reveals upper crustal contamination processes: new U–Pb ages, Hf and O isotopes, and trace elements from the Central Atlantic magmatic province (CAMP) - J. H. F. L. Davies; A. Marzoli; H. Bertrand; N. Youbi; M. Ernesto; N. D. Greber; M. Ackerson; G. Simpson; A.-S. Bouvier; L. Baumgartner; T. Pettke; F. Farina; et al. (Contributions to Mineralogy and Petrology, 2021)
Zircon occasionally crystallizes in evolved melt pockets in mafic large igneous province (LIP) magmas, and in these cases, it is used to provide high-precision age constraints on LIP events. The precision and accuracy of high-precision ages from LIPs are crucially important, because they may be implicated in mass extinctions. However, why zircon crystallizes in these magmas is not clearly understood, since their mafic compositions should limit zircon saturation. Here, we investigate the occurrence of zircon (and baddeleyite) in intrusive and extrusive mafic rocks from Central Atlantic Magmatic Province (CAMP) using petrography, trace-element analysis, Ti temperatures, Hf and oxygen isotopes, and high-precision U–Pb geochronology, along with petrological and thermal modeling. We provide new ages for CAMP sills that intruded into Paleozoic sediments in Brazil, indicating that the high and low Ti magmatism in this area occurred synchronously over 264 ± 57 ka. We show that upper crustal assimilation, especially of shales, during the emplacement of the CAMP likely led to zircon saturation. Assimilation of upper crustal sediments is also supported by high δ 18 O values and some rare negative εHf values in the zircon crystals. The only extrusive sample analyzed was the North Mountain basalt in Nova Scotia, Canada. This sample contains a large age variation in its zircon crystals (up to 4 Ma), and the older crystals have slightly more negative εHf values suggesting the presence of small (micron scale) xenocrystic cores associated with very late-stage sediment assimilation. However, the CAMP dataset as a whole suggests that the presence of xenocrystic cores is rare. Assuming no xenocrystic cores, and considering the zircon undersaturated nature of LIP mafic melts, the oldest zircon age clusters in a population should record the magma emplacement (or time when assimilation occurred), and the younger ages in a population are more likely to reflect Pb loss, especially given the high U concentrations of LIP zircon. Our identification of heterogeneous isotopic and elemental compositions in LIP zircon indicates that zircon in these magmas saturate in isolated minute melt pockets just before the system cools below its solidus.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Quantifying Soft Tissue Artefacts and Imaging Variability in Motion Capture of the Fingers - C. D. Metcalf; C. Phillips; A. Forrester; J. Glodowski; K. Simpson; C. Everitt; A. Darekar; L. King; D. Warwick; A. S. Dickinson (Annals of Biomedical Engineering, 2020)
This study assessed the accuracy of marker-based kinematic analysis of the fingers, considering soft tissue artefacts (STA) and marker imaging uncertainty. We collected CT images of the hand from healthy volunteers with fingers in full extension, mid- and full-flexion, including motion capture markers. Bones and markers were segmented and meshed. The bone meshes for each volunteer’s scans were aligned using the proximal phalanx to study the proximal interphalangeal joint (PIP), and using the middle phalanx to study the distal interphalangeal joint (DIP). The angle changes between positions were extracted. The HAWK protocol was used to calculate PIP and DIP joint flexion angles in each position based on the marker centroids. Finally the marker locations were ‘corrected’ relative to the underlying bones, and the flexion angles recalculated. Static and dynamic marker imaging uncertainty was evaluated using a wand. A strong positive correlation was observed between marker- and CT-based joint angle changes with 0.980 and 0.892 regression slopes for PIP and DIP, respectively, and Root Mean Squared Errors below 4°. Notably for the PIP joint, correlation was worsened by STA correction. The 95% imaging uncertainty interval was

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Understanding fish populations - S. D. Simpson; I. Barber; I. J. Winfield (Journal of Fish Biology, 2018)

Using exposure windows to explore an elusive biomarker: blood manganese - Marissa G. Baker; Bert Stover; Christopher D. Simpson; Lianne Sheppard; Noah S. Seixas (International Archives of Occupational and Environmental Health, 2016)

Molecular tools for bathing water assessment in Europe: Balancing social science research with a rapidly developing environmental science evidence-base - David M. Oliver; Nick D. Hanley; Melanie van Niekerk; David Kay; A. Louise Heathwaite; Sharyl J. M. Rabinovici; Julie L. Kinzelman; Lora E. Fleming; Jonathan Porter; Sabina Shaikh; Rob Fish; Sue Chilton; et al. (Ambio, 2016)

The influence of various reef sounds on coral‐fish larvae behaviour - E. Parmentier; L. Berten; P. Rigo; F. Aubrun; S. L. Nedelec; S. D. Simpson; D. Lecchini (Journal of Fish Biology, 2015)
The swimming behaviour of coral‐reef fish larvae from 20 species of 10 different families was tested under natural and artificial sound conditions. Underwater sounds from reef habitats (barrier reef, fringing reef and mangrove) as well as a white noise were broadcasted in a choice chamber experiment. Sixteen of the 20 species tested significantly reacted to at least one of the habitat playback conditions, and a range of responses was observed: fishes were (1) attracted by a single sound but repelled by none ( e.g. white‐banded triggerfish Rhinecanthus aculeatus was attracted by the barrier‐reef sound), (2) repelled by one or more sounds but attracted by none ( e.g. bridled cardinalfish Pristiapogon fraenatus was repelled by the mangrove and the bay sounds), (3) attracted by all sounds ( e.g . striated surgeonfish Ctenochaetus striatus ), (4) attracted and repelled by several sounds ( e.g . whitetail dascyllus Dascyllus aruanus was attracted by the barrier‐reef sound and repelled by the mangrove sound) and (5) not influenced by any sound ( e.g . convict surgeonfish Acanthurus triostegus ). Overall, these results highlight two settlement strategies: a direct selection of habitats using sound (45% of the species), or a by‐default selection by avoidance of certain sound habitats (35%). These results also clearly demonstrated the need to analyse the influence of sounds at the species‐specific level since congeneric and confamilial species can express different behaviours when exposed to the same sounds.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Vertical and horizontal distributions of coral‐reef fish larvae in open water immediately prior to reef colonization - D. Lecchini; V. P. Waqalevu; S. Holles; M. Lerohellec; C. Brie; S. D. Simpson (Journal of Fish Biology, 2013)
To explore the vertical and horizontal distributions of fish larvae near the end of their pelagic period, six light traps were set up over four lunar months at different depths (sub‐surface, midwater and bottom) and different habitat types (reef slope: 50 m horizontal distance from the reef crest; frontier zone: 110 m horizontal distance; sandy zone: 200 m horizontal distance) on the outer reef slope of Moorea Island, French Polynesia. The highest captures were in sub‐surface traps on the reef slope and the frontier zone, and in bottom traps on the sandy zone and the frontier zone. It is hypothesized that fish larvae move towards the surface near the reef slope to avoid reef‐based planktivores and to get into a favourable position for surfing over the reef crest.

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Juvenile coral reef fish use sound to locate habitats - C. A. Radford; J. A. Stanley; S. D. Simpson; A. G. Jeffs (Coral Reefs, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

A wide diversity of previously undetected free‐living relatives of diplomonads isolated from marine/saline habitats - Martin Kolisko; Jeffrey D. Silberman; Ivan Cepicka; Naoji Yubuki; Kiyotaka Takishita; Akinori Yabuki; Brian S. Leander; Isao Inouye; Yuji Inagaki; Andrew J. Roger; Alastair G. B. Simpson (Environmental Microbiology, 2010)
Summary Over the last 15 years classical culturing and environmental PCR techniques have revealed a modest number of genuinely new major lineages of protists; however, some new groups have greatly influenced our understanding of eukaryote evolution. We used culturing techniques to examine the diversity of free‐living protists that are relatives of diplomonads and retortamonads, a group of evolutionary and parasitological importance. Until recently, a single organism, Carpediemonas membranifera , was the only representative of this region of the tree. We report 18 new isolates of Carpediemonas ‐like organisms (CLOs) from anoxic marine sediments. Only one is a previously cultured species. Eleven isolates are conspecific and were classified within a new genus, Kipferlia n. gen. The remaining isolates include representatives of three other lineages that likely represent additional undescribed genera (at least). Small‐subunit ribosomal RNA gene phylogenies show that CLOs form a cloud of six major clades basal to the diplomonad‐retortamonad grouping (i.e. each of the six CLO clades is potentially as phylogenetically distinct as diplomonads and retortamonads). CLOs will be valuable for tracing the evolution of diplomonad cellular features, for example, their extremely reduced mitochondrial organelles. It is striking that the majority of CLO diversity was undetected by previous light microscopy surveys and environmental PCR studies, even though they inhabit a commonly sampled environment. There is no reason to assume this is a unique situation – it is likely that undersampling at the level of major lineages is still widespread for protists.

Paleolimnological evidence of the effects on lakes of energy and mass transfer from climate and humans - Peter R. Leavitt; S. C. Fritz; N. J. Anderson; P. A. Baker; T. Blenckner; L. Bunting; J. Catalan; D. J. Conley; W. O. Hobbs; E. Jeppesen; A. Korhola; S. McGowan; et al. (Limnology and Oceanography, 2009)
The premise of this article is that climate effects on lakes can be quantified most effectively by the integration of process‐oriented limnological studies with paleolimnological research, particularly when both disciplines operate within a common conceptual framework. To this end, the energy (E)‐mass ( m ) flux framework (E m flux) is developed and applied to selected retrospective studies to demonstrate that climate variability regulates lake structure and function over diverse temporal and spatial scales through four main pathways: rapid direct transfer of E to the lake surface by irradiance, heat, and wind; slow indirect effects of E via changes in terrestrial development and subsequent m subsidies to lakes; direct influx of m as precipitation, particles, and solutes from the atmosphere; and indirect influx of water, suspended particles, and dissolved substances from the catchment. Sedimentary analyses are used to illustrate the unique effects of each pathway on lakes but suggest that interactions among mechanisms are complex and depend on the landscape position of lakes, catchment characteristics, the range of temporal variation of individual pathways, ontogenetic changes in lake basins, and the selective effects of humans on m transfers. In particular, preliminary synthesis suggests that m influx can overwhelm the direct effects of E transfer to lakes, especially when anthropogenic activities alter m subsidies from catchments.

Restoring depleted coral‐reef fish populations through recruitment enhancement: a proof of concept - A. Heenan; S. D. Simpson; M. G. Meekan; S. D. Healy; V. A. Braithwaite (Journal of Fish Biology, 2009)
To determine whether enhancing the survival of new recruits is a sensible target for the restorative management of depleted coral‐reef fish populations, settlement‐stage ambon damsel fish Pomacentrus amboinensis were captured, tagged and then either released immediately onto small artificial reefs or held in aquaria for 1 week prior to release. Holding conditions were varied to determine whether they affected survival of fish: half the fish were held in bare tanks (non‐enriched) and the other half in tanks containing coral and sand (enriched). Holding fish for this short period had a significantly positive effect on survivorship relative to the settlement‐stage treatment group that were released immediately. The enrichment of holding conditions made no appreciable difference on the survival of fish once released onto the reef. It did, however, have a positive effect on the survival of fish while in captivity, thus supporting the case for the provision of simple environmental enrichment in fish husbandry. Collecting and holding settlement‐stage fish for at least a week before release appear to increase the short‐term survival of released fish; whether it is an effective method for longer‐term enhancement of locally depleted coral‐reef fish populations will require further study.

Renal injury at first presentation as a predictor for poor outcome in severe paracetamol poisoning referred to a liver transplant unit - N. Pakravan; K. J. Simpson; W. S. Waring; C. M. Bates; D. N. Bateman (European Journal of Clinical Pharmacology, 2009)

Urban geochemistry: research strategies to assist risk assessment and remediation of brownfield sites in urban areas - I. Thornton; M. E. Farago; C. R. Thums; R. R. Parrish; R. A. R. McGill; N. Breward; N. J. Fortey; P. Simpson; S. D. Young; A. M. Tye; N. M. J. Crout; R. L. Hough; et al. (Environmental Geochemistry and Health, 2008)

Effect of Nutrition on Toxicity of Contaminants to the Epibenthic Amphipod Melita plumulosa - D. A. Spadaro; T. Micevska; S. L. Simpson (Archives of Environmental Contamination and Toxicology, 2008)

Effect of Nutrition on Toxicity of Contaminants to the Epibenthic Amphipod Melita plumulosa - D. A. Spadaro; T. Micevska; S. L. Simpson (Archives of Environmental Contamination and Toxicology, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Nocturnal relocation of adult and juvenile coral reef fishes in response to reef noise - S. D. Simpson; A. Jeffs; J. C. Montgomery; R. D. McCauley; M. G. Meekan (Coral Reefs, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Effects of Light on Microalgae Concentrations and Selenium Uptake in Bivalves Exposed to Selenium-Amended Sediments - D. Schlenk; G. Batley; C. King; J. Stauber; M. Adams; S. Simpson; W. Maher; J. T. Oris (Archives of Environmental Contamination and Toxicology, 2007)

Bushiness and cytokinin profile in dormant and sprouting tubers of Zantedeschia - S. M. D’Arth; S. I. Simpson; J. F. Seelye; P. E. Jameson (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

The development and mapping of functional markers in Fragaria and their transferability and potential for mapping in other genera - D. J. Sargent; A. Rys; S. Nier; D. W. Simpson; K. R. Tobutt (Theoretical and Applied Genetics, 2006)

Effects of Sewage Sludge Disposal on Metal Content in the Sediment and Water of Mitchell Lake, San Antonio, Texas, USA - N. Simpson; D. Sarkar; R. Datta; S. Sharma (Bulletin of Environmental Contamination and Toxicology, 2006)

An enhanced microsatellite map of diploid Fragaria - D. J. Sargent; J. Clarke; D. W. Simpson; K. R. Tobutt; P. Arús; A. Monfort; S. Vilanova; B. Denoyes-Rothan; M. Rousseau; K. M. Folta; N. V. Bassil; N. H. Battey (Theoretical and Applied Genetics, 2006)

Measurements of Trace Gases in the Inflow of South China Sea Background Air and Outflow of Regional Pollution at Tai O, Southern China - T. Wang; H. Guo; D. R. Blake; Y. H. Kwok; I. J. Simpson; Y. S. Li (Journal of Atmospheric Chemistry, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Induction of heat shock protein 70 in rat olfactory epithelium by toxic chemicals: in vitro and in vivo studies - S. A. Simpson; D. J. Alexander; C. J. Reed (Archives of Toxicology, 2005)

Comparison of reference genes for quantitative real-time polymerase chain reaction analysis of gene expression in sugarcane - Hayati M. Iskandar; Robert S. Simpson; Rosanne E. Casu; Graham D. Bonnett; Donald J. Maclean; John M. Manners (Plant Molecular Biology Reporter, 2004)

An Assessment of Five Australian Polychaetes and Bivalves for Use in Whole-Sediment Toxicity Tests: Toxicity and Accumulation of Copper and Zinc from Water and Sediment - C. K. King; M. C. Dowse; S. L. Simpson; D. F. Jolley (Archives of Environmental Contamination and Toxicology, 2004)

Role of the Land Plume in the Transport of Ozone Over the Ocean During Indoex (1999) - M. D. Simpson; S. Raman (Boundary-Layer Meteorology, 2004)

Do early life history characteristics determine species ranges and dispersal of coral reef fishes in the Indo‐Pacific? - M. A. Priest; S. D. Simpson; C. Dytham (Journal of Fish Biology, 2003)
The Indo‐Pacific consists of extensive continuous coastlines and many island groups of varying sizes and isolation. The species ranges of coral reef fishes vary enormously from Indo‐Pacific wide to highly endemic. There is also great variation in the early life history characteristics of coral reef fishes ( e.g . pelagic larval durations, spawning strategies and swimming abilities). We use individual‐based models (IBMs) to simulate the dispersal of coral reef fishes in the Indo‐Pacific. The development of dispersal strategies is explored based on ecological and geographical constraints. Simulations are presented for climatic and anthropogenically‐induced events.

Does behaviour explain the larval dispersal of coral reef fishes better than oceanography?– An individual based model simulation approach - S. D. Simpson; C. Dytham; M. G. Meekan (Journal of Fish Biology, 2003)
Until recently, oceanographic models have been used, with limited success, to predict the larval dispersal of coral reef fishes. Settlement‐stage larvae have been shown to be capable swimmers and have highly developed sensory organs. We built two simulation individual based models (IBMs) of larval dispersal in the Dampier Archipelago, Western Australia. One followed an oceanographic model, while the other was driven by behavioural constraints. We compare predictions of these models with an extensive dataset from a light‐trapping programme in an attempt to elucidate the overriding mechanism of larval coral reef fish dispersal.

Plant collecting spread and densities: their potential impact on biogeographical studies in Thailand - J. A. N. Parnell; D. A. Simpson; J. Moat; D. W. Kirkup; P. Chantaranothai; P. C. Boyce; P. Bygrave; S. Dransfield; M. H. P. Jebb; J. Macklin; C. Meade; D. J. Middleton; et al. (Journal of Biogeography, 2003)
Aims To produce representative aggregate maps of plant collection locations in Thailand and discuss their impact on biogeographical studies in Thailand and the surrounding region. Location Thailand. Methods A representative data set comprising 6593 plant specimen records for Thailand has been assembled. The data set contains ± all known collections for fifteen representative plant families and further records for another 104. All records are localized to Changwat (province), 6441 to at least quarter degree square. Results Analysis shows that the spread of collecting activity in Thailand is markedly uneven; 20% of collections come from a single Changwat (Chiang Mai) and 53% of Changwat have fifty or fewer collections. The distribution of collections by Changwat and by quarter degree square is erratic with most squares and Changwat having few collections, both in proportionate and absolute terms. Some of the most densely forested Changwats and squares appear undercollected. Distribution maps for common, easily recognized tree species in the genus Syzygium show distributional gaps. Conclusions Thailand is defined as an undercollected country. Even within the few well‐collected quarter degree squares the spread of collecting is still poor; almost all collections being localized to one of three mountain ranges or their foothills. There are many gaps in collecting activity which make impossible a straightforward interpretation of biogeographical pattern. It is argued that targeted collecting activity is needed, that assembly of this type of data set is therefore essential and that our data set and its interpretation is a model for all countries in the region.

Microphysics, radiation and surface processes in the Goddard Cumulus Ensemble (GCE) model - Wei-Kuo Tao; J. Simpson; D. Baker; S. Braun; M.-D. Chou; B. Ferrier; D. Johnson; A. Khain; S. Lang; B. Lynn; C.-L. Shie; D. Starr; et al. (Meteorology and Atmospheric Physics, 2003)

Reproducibility of the blood lactate threshold, 4 mmol·l -1 marker, heart rate and ratings of perceived exertion during incremental treadmill exercise in humans - Grant S.; McMillan K.; Newell J.; Wood L.; Keatley S.; Simpson D.; Leslie K.; Fairlie-Clark S. (European Journal of Applied Physiology, 2002)

Aircraft Measurements of Dimethyl Sulfide (DMS) Using a Whole Air Sampling Technique - I. J. Simpson; J. J. Colman; A. L. Swanson; A. R. Bandy; D. C. Thornton; D. R. Blake; F. S. Rowland (Journal of Atmospheric Chemistry, 2001)

Somaclonal variation in cryopreserved embryogenic clones of white spruce [ Picea glauca (Moench) Voss.] - L. L. DeVerno; Y. S. Park; J. M. Bonga; J. D. Barrett; C. Simpson (Plant Cell Reports, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Recovery of benthic communities at Macquarie Island (sub-Antarctic) following a small oil spill - S. D. A. Smith; R. D. Simpson (Marine Biology, 1998)

Why do some females reject males? The molecular basis for male-specific graft rejection - D. M. Scott; I. E. Ehrmann; P. S. Ellis; P. R. Chandler; E. Simpson (Journal of Molecular Medicine, 1997)

Congo/Crimean Haemorrhagic Fever virus from Iraq 1979: I. Morphology in BHK21 cells - D. S. Ellis; T. Southee; G. Lloyd; G. S. Platt; Nicola Jones; Susan Stamford; E. T. W. Bowen; D. I. H. Simpson (Archives of Virology, 1981)